Study protocol of psychometric properties of the Spanish translation of a competence test in evidence based practice: The Fresno test - Villafafila-Ferrero Rosa; Margalef-Pallarès Francesc; Pérez-Rodríguez Belén; Fuentes-Bellido Cruz M; Juncosa Sebastià; Bundó-Vidiella Magda; Foz Gonçal; Pujol-Ribera Enriqueta; Jiménez-Villa Josep; Flores-Mateo Gemma; Argimon-Pallàs Josep M; Forès-Garcia Dolors; et al. (BMC Health Services Research, 2009)
Abstract Background There are few high-quality instruments for evaluating the effectiveness of Evidence-Based Practice (EBP) curricula with objective outcomes measures. The Fresno test is an instrument that evaluates most of EBP steps with a high reliability and validity in the English original version. The present study has the aims to translate the Fresno questionnaire into Spanish and its subsequent validation to ensure the equivalence of the Spanish version against the English original. Methods and design The questionnaire will be translated with the back translation technique and tested in Primary Care Teaching Units in Catalonia (PCTU). Participants will be: (a) tutors of Family Medicine residents (expert group); (b) Family Medicine residents in their second year of the Family Medicine training program (novice group), and (c) Family Medicine physicians (intermediate group). The questionnaire will be administered before and after an educational intervention. The educational intervention will be an interactive four half-day sessions designed to develop the knowledge and skills required to EBP. Responsiveness statistics used in the analysis will be the effect size, the standardised response mean and Guyatt's method. For internal consistency reliability, two measures will be used: corrected item-total correlations and Cronbach's alpha. Inter-rater reliability will be tested using Kappa coefficient for qualitative items and intra-class correlation coefficient for quantitative items and the overall score. Construct validity, item difficulty, item discrimination and feasibility will be determined. Discussion The validation of the Fresno questionnaire into different languages will enable the expansion of the questionnaire, as well as allowing comparison between countries and the evaluation of different teaching models.